Modelling of outdoor natural ventilation and energy performance for buildings in an industrial park : effect of the urban-heat-island - Teh, Phyllis Fei Yin (Nanyang Technological University, 2021)
The urban air temperature is slowly rising in cities around the world. The leading causes of this effect include low wind velocity due to high-building density, diminishing of green areas, and change of surface coating materials. This may lead to overheating from human activities and absorption of solar radiation on dark surfaces. This problem is further worsened by increasing demand on air-conditioning, which again leads to additional heating and carbon dioxide release. [1] The main objective of the work presented in this report is to perform Computational Fluid Dynamics (CFD) simulation studies to investigate the airflow patterns within an industrial estate and to attempt to find ways to improve the airflow. In total, 6 CFD simulations were carried out to study the flow behavior within the estate. These 6 studies comprise of: 1. Reference model (North wind) 2. Reference model (East wind) 3. Model no. 1 - Bisected reference model (North wind) 4. Model no. 1 - Bisected reference model (East wind) 5. Model no. 2 – Model no. 1 with expanded driveway (North wind) 6. Model no. 2 – Model no. 1 with expanded driveway (East wind) For studies no. 1 and 2, a reference model was replicated after the Toa Payoh industrial park. The reference model consists of 11 industrial blocks (block no. 1 to 8 and 10 to 12) and 1 canteen (block no. 9). For studies no. 3 and 4, the reference model was reshaped such that all the industrial blocks were divided into 2 equal parts. The rationale behind this is that when the blocks are divided and spaced out, gaps are formed. In theory, this would encourage airflow. Finally, for studies no. 5 and 6, the bisected model was modified again. This time, the driveways were expanded from single-lane road to two-lane road, so as to further increase the gaps in between the industrial blocks. For all North-wind studies, the velocity inlet boundary condition is set on the North-side surface. Similarly, for East-wind studies, the velocity inlet is set on the East-side surface.